Study of Contour and Slope of Mohupomba Island Region Using QGIS Application for Sustainable Agricultural Development - Ayu Rosandi Dg Mansyur; Nurdin, Nurdin; Nurmi, Nurmi (International journal of technology and education research, 2025)
Understanding the important characteristics of the topography of Mohupomba Island through contour and slope analysis using the QGIS application is the focus of this study. This study aims to identify variations in elevation and slope to support sustainable land use planning, particularly for agricultural development and disaster mitigation. The method used was qualitative descriptive with stages of collecting DEMNAS Geospatial Data from the Geospatial Information Agency (BIG) to obtain accurate elevation information, data processing using QGIS version 3.40, and visual analysis of contour and slope maps. The results showed that Mohupomba Island has an elevation range of 0–17 meters above sea level (masl), with a dense contour pattern in the eastern region indicating steep slopes, while the western part tends to be gentle. Most of the area is dominated by flat (0–8%) and gentle (8–15%) slopes, which are suitable for agricultural activities using soil conservation techniques. Meanwhile, areas with slopes >45% are classified as very steep and have a high potential for erosion and landslides, so they are not recommended for agricultural land development.